Assessing the impact of the covid-19 pandemic on the colombian industrial sector: a multivariate time series analysis (2023)
The Coronavirus Disease 2019 (COVID-19) pandemic has had a severe impact on the global economy, and Latin America and the Caribbean were no exceptions. Colombia faced unprecedented economic and public health crises, leading to a significant reduction in its gross domestic product (GDP) and exportation rate of goods and services. In this study, we explore the pandemic's effect on the Colombian industrial sector using official data and statistics. We analyze the monthly Industrial Production Index (IPI) measurements taken by the Colombian National Administrative Department of Statistics (DANE, for its Spanish acronym) for 22 national industrial subsectors between January 2005 and December 2021. We apply multivariate statistics and time series techniques to compare forecasts with actual responses of the most affected subsectors after the COVID-19 outbreak. Our findings suggest that the Colombian industrial sector was not well-prepared to face the pandemic, leading to a significant financial loss. We also observe that the developing countries' industrial sectors, like Colombia's, are highly exposed and vulnerable. This information can help policymakers in Colombia to better understand the weaknesses of the industrial sector and develop strategies to mitigate the impact of future crises.